2014
DOI: 10.1002/asia.201402535
|View full text |Cite
|
Sign up to set email alerts
|

Exfoliation of Graphite into Graphene in Polar Solvents Mediated by Amphiphilic Hexa‐peri‐hexabenzocoronene

Abstract: A water-soluble surfactant consisting of hexa-peri-hexabenzocoronene (HBC) as hydrophobic aromatic core and hydrophilic carboxy substituents was synthesized. It exhibited a self-assembled nanofiber structure in the solid state. Profiting from the π interactions between the large aromatic core of HBC and graphene, the surfactant mediated the exfoliation of graphite into graphene in polar solvents, which was further stabilized by the bulky hydrophilic carboxylic groups. A graphene dispersion with a concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 36 publications
1
9
0
1
Order By: Relevance
“…In another example, HBC molecules on graphitic substrates were found to have different growth modes such as layer‐by‐layer growth, [272] columns [273] and others. Further application of an HBC carrying a carboxylic group was shown to exfoliate graphite into graphene in polar solvents [274] . This feature was due to the pressence of a hydrophobic aromatic core and a hydrophilic carboxy substituents, installed at the periphery of the aromatic core.…”
Section: Resultsmentioning
confidence: 99%
“…In another example, HBC molecules on graphitic substrates were found to have different growth modes such as layer‐by‐layer growth, [272] columns [273] and others. Further application of an HBC carrying a carboxylic group was shown to exfoliate graphite into graphene in polar solvents [274] . This feature was due to the pressence of a hydrophobic aromatic core and a hydrophilic carboxy substituents, installed at the periphery of the aromatic core.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, this graphene dispersion led to 20% sedimentation after one week. Recently, we reported the LPE of graphene in polar solvents mediated by a novel water-soluble surfactant consisting of hexa-peri-hexabenzocoronene (HBC) as a hydrophobic aromatic core and hydrophilic carboxy substituents [42]. Resulting from the strong interactions between the large aromatic core and the graphene surface, a graphene dispersion with a concentration of 1.1 mg/mL in methanol containing 2-6 multilayer nanosheets was obtained.…”
Section: Liquid-phase Exfoliation (Lpe)mentioning
confidence: 98%
“…Thus, the solution‐phase methods that can produce defect‐free, unoxidized graphene in large scale are highly expected. In a facile and direct manner, graphene nanosheets can be obtained through exfoliating pristine graphite dispersed in ionic liquid, organic solvents, inorganic salts, surfactant solutions, or their mixed‐solvent. For example, Coleman et al successfully demonstrated that graphene dispersions with concentrations up to 0.01 mg mL −1 could be produced by dispersion and exfoliation of graphite in organic solvents such as N ‐methyl‐pyrrolidone due to the matched surface energies of solvent and graphene .…”
Section: Synthesis Of Graphene and Their Composite Photocatalystsmentioning
confidence: 99%